Capitalismo e burocracia: economia e política nas Relações agrárias na Antigüidade, de Max Weber - Joly, Fábio Duarte (Revista de História, 1999)
The aim of this article is to discuss the methodological and political guidelines of Max Weber's theory of ancient capitalism as elaborated in his Agrarian relations in Antiquity.